Feedback and Trigger of Household Decision-Making to Ecological Protection Policies in Sanjiangyuan National Park - Su, Xukun; Shen, Yu; Dong, Shikui; Liu, Yuqing; Cheng, Hao; Wan, Lingfan; Liu, Guohua (Frontiers in Plant Science, 2022)
Ignoring responses of local households to ecological protection policies can not only seriously limit sustainable development of the alpine grassland ecosystem, but also can not improve livelihood and well-being of local households on the Qinghai-Tibetan Plateau (QTP). It is necessary to clearly understand coupling feedback and trigger between household decision-making of local herdsmen with implementation of ecological protection policies. We selected Sanjiangyuan National Park (SNP) as the study area which was in the hinterland of the Qinghai-Tibet Plateau and the first national park in China. We used global rangeland model (G-Range model) to simulate changes of alpine grassland and DEcisions under Conditions of Uncertainty by Modeled Agents model (DECUMA model) to identify household decision-making of local herdsmen. Results showed that: (1) distribution of livestock density was basically consistent with distribution of habitat suitability of local households in the SNP; (2) more than a half of the uneducated households (52% and 70%) opposed the eco-compensation and eco-migration policies; (3) most of households (53.68%) never chose to trade livestock for maintaining livelihood; and (4) 65 thousands yuan (≈10 thousand dollars) in debts as the critical value (trigger), local households selected to trade livestocks to support their livelihood. We suggest that feedback and trigger of household decision-making should be fully considered by managers of national park and policy-makers of local governments in planning ecological protection policies to maintain sustainable development of alpine grassland, which is of practical significance to long-term conservation and sustainable utilization of natural resources in the SNP.